Factors Influencing Job Satisfaction Among Employees in Aspiro Solutions Sdn.Bhd - Elangovan , Sasmithaa; Suppramaniam, Subaashnii; Dada , Morakinyo (Electronic Journal of Business and Management, 2023)
This study aims to determine the effects of independent variables on dependent variables by examining the relationships between compensation, work-life balance, performance recognition, career development opportunities, work environment, and job satisfaction of employees at Aspiro Solutions Sdn Bhd. It also aims to demonstrate to managers, regular employees, and supervisors the value that Aspiro Solutions Sdn Bhd employees place on things like compensation, work-life balance, performance recognition, career development opportunities, and the work environment. The findings of this study indicate that Aspiro Solutions Sdn Bhd organization now has a better understanding of their regular employees, managers, and supervisors’ level of job satisfaction. To increase the job satisfaction of their employees, Aspiro Solutions Sdn Bhd placed a lot of attention on the importance of these independent variables (compensation, work-life balance, performance recognition, career development opportunities, and work environment).